Sonographic assessment of fetal occiput position during labor for the prediction of labor dystocia and perinatal outcomes. (16th December 2016) - Choi, Sae Kyung; Park, Yong Gyu; Lee, Da Hye; Ko, Hyun Sun; Park, In Yang; Shin, Jong Chul
Abstract: Objectives : To evaluate the effect of the occiput posterior (OP) position on dystocia and perinatal outcomes. Methods : This was a prospective cohort study of 162 primiparous women. We performed intrapartum sonography, and fetal occiput positions were recorded. The relationships between the position of the occiput and the course of labor and perinatal outcomes were investigated. Statistical analysis was performed using SAS 9.2. Results : Fifty-six of 162 fetuses were found to be in the OP position during the first stage of labor. Eight (80.0%) of 10 fetuses in the OP position during the second stage were among the 56 that were in OP position during the first stage. The rate of cesarean sections performed in the OP position group during the first stage was significantly higher than the rate in the non-OP position group (37.5% versus 8.5%, p < 0.0001). The duration of the second stage of labor was longer and neonatal complications occurred more frequently in the OP position group during the second stage than in the non-OP position group (77.9 ± 33.4 min versus 52.2 ± 26.6 min, p = 0.0104; 50.0% versus 17.2%, p = 0.0118). Conclusions : The OP position may be a useful predicator for labor dystocia that can lead to poor neonatal outcomes.